2013
DOI: 10.1002/pola.26815
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyacrylonitrile via SET-LRP catalyzed by lanthanum powder in the presence of VC

Abstract: A novel catalyst system based on La(0)/hexamethylenetetramine (HMTA) complexes is used for single electron transfer-living radical polymerization (SET-LRP) of acrylonitrile (AN) in the presence of ascorbic acid (VC) with carbon tetrachloride (CCl 4 ) as a initiator and N,N-dimethylformamide (DMF) as a solvent. Compared with SET-LRP of AN in the absence of VC, monomer conversion is markedly increased. SET-LRP of AN in the presence of VC is also conducted in the presence of air. The kinetic studies show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The initial reports on SET-LRP involve activation, almost exclusively, by zerovalent copper or copper derivatives. However, in the last two years several groups have investigated alternative metallic catalytic sources, including silver (Ag), iron (Fe), nickel (Ni), ytterbium (Yb), lanthanum (La), , gadolinium (Gd), magnesium (Mg), tin (Sn), and samarium (Sm) . For instance, Fe is highly attractive as it is inexpensive, nontoxic, abundant, environmentally benign, biocompatible, and easy to remove.…”
Section: Dynamics Of Set-lrpmentioning
confidence: 99%
“…The initial reports on SET-LRP involve activation, almost exclusively, by zerovalent copper or copper derivatives. However, in the last two years several groups have investigated alternative metallic catalytic sources, including silver (Ag), iron (Fe), nickel (Ni), ytterbium (Yb), lanthanum (La), , gadolinium (Gd), magnesium (Mg), tin (Sn), and samarium (Sm) . For instance, Fe is highly attractive as it is inexpensive, nontoxic, abundant, environmentally benign, biocompatible, and easy to remove.…”
Section: Dynamics Of Set-lrpmentioning
confidence: 99%
“…115 Matyjaszewski and co-workers reported the polymerization of MA mediated by a zero-valent metal wire (zinc, magnesium, and iron) combined with CuBr 2 in DMSO at 25 C. 37 Chen et al also have dedicated research toward a series of other zero-valent metal catalyzed RDRPs. For example, RDRPs of MMA with ytterbium powder [Yb(0)] 116 and gadolinium powder [Gd(0)] 117 as catalyst, and RDRPs of AN catalyzed with samarium powder [Sm(0)], 92 tin powder [Sn(0)], 118 lanthanum powder [La(0)], 119,120 magnesium powder [Mg(0)] 121 and so on. These studies have all played a crucial role in extending the applications of RDRP.…”
Section: Catalyst Systemmentioning
confidence: 99%
“…The haloforms, CHCl 3 , 9,122 CHBr 3 , 9,126 and CHI 3 , 9,126 have been employed as initiators for the zero-valent metal-mediated RDRP of MA in DMSO at 25 C. Among these compounds, CHCl 3 and CHBr 3 are always monofunctional initiators, however, CHI 3 is only a monofunctional initiator for PMA at low conversion and transitions to a bifunctional initiator at high conversion. CHBr 3 has also been demonstrated as an effective initiator for the zerovalent metal-mediated RDRP of VC in DMSO at 25 by Percec et al 9,14 The RDRP process has been evaluated for the Cu(0) wire catalyzed polymerization of MMA using inexpensive and readily available CCl 4 as an initiator, with the reaction driven to completion in 10 h at 25 C. 127 Chen et al have also reported other zero-valent metal (such as Yb(0), 116 Sn(0) 118 and La(0) 119,120 ) catalyzed RDRPs of MMA or AN with CCl 4 as an initiator.…”
Section: Initiatorsmentioning
confidence: 99%
“…The novel catalyst system based on La(0)/HMTA had been developed by our laboratory, and proven to be superior to the traditional catalyst system . In addition, we had also reported that the addition of a small amount of VC to the reaction mixture significantly increased the reaction rate and the controllability of the polymer . The monomer conversion (C%) increased reaching about 23% within 24 h. Figure shows kinetic plots of ln([M] 0 /[M]) versus reaction time.…”
Section: Resultsmentioning
confidence: 99%
“…35 In addition, we had also reported that the addition of a small amount of VC to the reaction mixture significantly increased the reaction rate and the controllability of the polymer. 36 The monomer conversion (C%) increased reaching about 23% within 24 h. Figure 1 shows kinetic plots of ln([M] 0 /[M]) versus reaction time. The apparent rate constant for SET-LRP of AN was calculated to be 2.9 × 10 −6 s −1 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%